Bending Behaviour of Post-tensioned Interlocking Block Masonry Wall - Muda Z.C.; Naganthan S.; Balasingam V.B.; Beddu S.; Sadon S.N. (EDP Sciences, 2023)
Environmental engineering; Offshore oil well production; Reinforcement; Soils; Walls (structural partitions); Bending behaviour; Cracking patterns; Environmental quality; House construction; Load deflection; Modern techniques; Post tensioned; Production cost; Brick